The Most Possible Scheme of Joint Service Detection for the Next Wireless Communication Technologies - Hendra Setiawan; Firdaus Firdaus (Universitas Ahmad Dahlan, 2013)
The era of beyond third generation wireless communication is highly heterogeneous in that it comprises several radio access technologies that need to be joined into a single multimode terminal. In this respect, this paper introduces a common service recognition system for the next wireless communication technologies i.e. Long Term Evolution (LTE), WiMAX or IEEE 802.16, and Wireless Local Area Network (WLAN) or IEEE 802.11.It is done in physical layer as one of multimode terminal ability regardless network cooperation existence. We investigation the preamble and synchronization signals as indicators of the available services instead of carrier frequency detection. To detect these signals, we proposed a time domain detection system consisting of auto-correlation, cross-correlation, and a peak period detection. Based on complexity analysis, this paper proposes the most possible scheme with lower complexity than cross-correlation implementation. Moreover, the fixed point simulation results show that the proposed system satisfies the minimum receiver sensitivity requirements that specified in the standards.